2010
DOI: 10.1007/s00439-010-0790-y
|View full text |Cite
|
Sign up to set email alerts
|

Kalirin: a novel genetic risk factor for ischemic stroke

Abstract: Cerebrovascular and cardiovascular diseases are the leading causes of death and disability worldwide. They are complex disorders resulting from the interplay of genetic and environmental factors, and may share several susceptibility genes. Several recent studies have implicated variants of the Kalirin (KALRN) gene with susceptibility to cardiovascular and metabolic phenotypes, but no studies have yet been performed in stroke patients. KALRN is involved, among others, in the inhibition of inducible nitric oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 34 publications
(40 reference statements)
0
32
0
Order By: Relevance
“…Interestingly, detailed examination of clinical information from the first sample set, which was uniquely available to us, revealed that congenital or early-onset vascular disease was observed in 5 of 7 cases with P2255T (supplementary table S1). Because KALRN may represent a candidate gene for vascular diseases, 31,32 it is tempting to speculate that P2255T may be a potential risk factor for vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, detailed examination of clinical information from the first sample set, which was uniquely available to us, revealed that congenital or early-onset vascular disease was observed in 5 of 7 cases with P2255T (supplementary table S1). Because KALRN may represent a candidate gene for vascular diseases, 31,32 it is tempting to speculate that P2255T may be a potential risk factor for vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The ascertainment and collection criteria for study participants, the DNA extraction and genotyping protocols, as well as the statistical analyses have been described in detail previously [5]. The research protocol was approved by the Ethics Committees of participating institutions.…”
Section: Methodsmentioning
confidence: 99%
“…18,24,25 Wu et al 16 established Kalirin as a signaling protein that specifically promotes Rac1 activation and contributes to VSMC migration downstream of PDGF in vitro. Importantly, the authors demonstrate that decreased Kalirin expression in vivo significantly reduced neointimal formation in a model of arterial endothelial denudation.…”
Section: See Accompanying Article On Page 702mentioning
confidence: 99%